Influence of atmospheric stability on wind farm performance in complex terrain. (15th January 2021) - Radünz, William Corrêa; Sakagami, Yoshiaki; Haas, Reinaldo; Petry, Adriane Prisco; Passos, Júlio César; Miqueletti, Mayara; Dias, Eduardo
Abstract: Viabilized by observations from modern field experiments in complex terrain sites, wind energy models have been enhanced to incorporate the unsteadiness of the diurnal cycle and the influence of atmospheric stability. Their ultimate goal is to accurately estimate the energy production performance of wind farm projects throughout their lifetime. There is still a research gap on the influence of the wind conditions reported by those experiments on the power performance of wind farms, the question that motivated these experiments in the first place. Thus, this paper reports an investigation of the influence of atmospheric stability on the power performance of two similar wind farms built over a plateau using observations from a recent measurement campaign at that site. Performance is herein the relative difference in mean power between the front and back rows of turbines. At both farms, the back rows underperform during the daytime hours (−10%/−8%) and in unstable conditions (−11%/−3%). Conversely, a significant inversion in performance occurs during the nighttime hours (23%/23%) and in stable conditions (33%/37%), whereby the back rows overperform. The combined effect of nighttime hours and stable conditions leads to even higher overperformances (35%/39%). The main underlying cause for performance variations is possibly the interplay between atmospheric stability and flow patterns on the windward slope and leeward side, rather than in the wakes. Thus, the wind power plants of the future should be designed with models that accurately incorporate flow phenomena that are related to atmospheric stability and the diurnal cycle. Highlights: Performance differences between two rows of turbines are assessed at two wind farms. Frontrows outperform backrows during unstable conditions of the daytime period. Backrows outperform frontrows during very stable conditions of the nighttime period. Wind patterns and atmospheric stability are the probable underlying cause. Wakes are likely not responsible for aforementioned performance differences.